Hubungan antara Intrinsic Religiousness, Attitude toward Digital Piracy, dan Intention to Commit Digital Piracy - Ari Irawan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This study aims to (1) find out the effect of Intrinsic Religiousness on Attitude toward Digital Piracy (2) find out the effect of Intrinsic Religiousness on Intention to Commit Digital Piracy (3) find out the effect of Attitude toward Digital Piracy on Intention to Commit Digital PiracyThe type of research used is associative with a quantitative approach. The population in this study were 2013-2018 students of Universitas Brawijaya who using Microsoft Office and worship in mosques on the main campus of Universitas Brawijaya. The sample used in this study was 115 respondents taken by using purposive sampling and data collection methods using questionnaires. Data analysis used is descriptive statistical analysis and path analysis (path analysis). The data in this study were processed using SPSS. The results of this research show that Intrinsic Religiousness (x) has a significant on Attitude toward Digital Piracy (z) and Intention to Commit Digital Piracy (y), moreover Attitude toward Digital Piracy (z) have a significant effect on Intention to Commit Digital Piracy (y).